Application of Alginate-Based Edible Coating with Beeswax Addition on Minimally Processed Pears (Pyrus bretschneideri Rehd.) - Maftukh Zaina Luthfiyyah; Esa Ghanim Fadhallah; Novita Herdiana; Fibra Nurainy (Biology, Medicine, & Natural Product Chemistry, 2025)
Pears, especially after being cut, tended to experience a decline in quality and damage such as enzymatic browning, moisture loss, and texture changes. The application of alginate-based edible coating with the addition of beeswax was one of the innovations that could be applied to minimally processed pears to slow down the rate of deterioration. This study aimed to determine the effect of beeswax concentration in alginate-based edible coating solutions on the freshness of minimally processed pears and to identify the optimal beeswax concentration using the star method. The study was designed using a Completely Randomized Design (CRD) in a non-factorial arrangement with the addition of beeswax. The treatments consisted of six levels: BK as the control, B0 (alginate), B2 (alginate + 2% beeswax), B4 (alginate + 4% beeswax), B6 (alginate + 6% beeswax), and B8 (alginate + 8% beeswax), each with four replications. The results showed that the addition of beeswax to the alginate-based edible coating had a significant effect on moisture content, weight loss, firmness, total soluble solids, and color. The best treatment for maintaining pear freshness according to the star method was B4 (4% beeswax), which had a moisture content of 85.66%, weight loss of 1.79%, firmness of 874.63 gf, total soluble solids of 11.28 ËšBrix, and a lightness (L) value of 68.30 on day 12 of storage.